2008
DOI: 10.1007/s00454-008-9057-y
|View full text |Cite
|
Sign up to set email alerts
|

Empty Simplices of Polytopes and Graded Betti Numbers

Abstract: Abstract. The conjecture of Kalai, Kleinschmidt, and Lee on the number of empty simplices of a simplicial polytope is established by relating it to the first graded Betti numbers of the polytope. The proof allows us to derive explicit optimal bounds on the number of empty simplices of any given dimension. As a key result, we prove optimal bounds for the graded Betti numbers of any standard graded K-algebra in terms of its Hilbert function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In Proposition 3.6 of [13], Kalai proved the special case of the following corollary for polytopal spheres. Also, in Corollary 4.8 of [19], Nagel proved the special case of this corollary for homology spheres with the Weak Lefschetz Property (WLP). Conjecturally, all homology spheres have WLP.…”
Section: Bistellar Moves and Shelling Movesmentioning
confidence: 97%
“…In Proposition 3.6 of [13], Kalai proved the special case of the following corollary for polytopal spheres. Also, in Corollary 4.8 of [19], Nagel proved the special case of this corollary for homology spheres with the Weak Lefschetz Property (WLP). Conjecturally, all homology spheres have WLP.…”
Section: Bistellar Moves and Shelling Movesmentioning
confidence: 97%
“…It was shown by Kalai [Ka2,Proposition 3.6] and Nagel [Na,Corollary 4.6] that if ∆ is an (r − 1)stacked homology (d − 1)-sphere and r ≤ d 2 then ∆ has no missing k-faces for r ≤ k ≤ d − r (they write statements only for polytopes but this fact for homology spheres follows from Nagel's proof since an (r − 1)-stacked homology (d − 1)-sphere with r ≤ d 2 has the weak Lefschetz property and satisfies h r−1 = h r ). This fact can be generalized as follows.…”
Section: Vanishing Of Missing Facesmentioning
confidence: 94%
“…In order to identify the facets in the unique (k + 1)-stacked triangulation S(D a ) of D a , we first identify the missing faces of D a , namely its minimal non-faces. Kalai [Kal94] and Nagel [Nag08] showed that if g i (R) 0 for a simplicial j-polytope R, then R has no missing ℓ-faces for i ≤ ℓ ≤ j − i . Combined with the simplicial GLBT, a subset A of d vertices of D a is a facet in S(D a ) iff all its subsets B of size ∂T * ast x (Lex a (C)).…”
Section: No Obvious Cubical Glbtmentioning
confidence: 99%